Distinctive distribution and migration of global fallout plutonium isotopes in an alpine lake and its implications for sediment dating. (September 2021) - Guo, Haiting; Xu, Yihong; Pan, Shaoming; Liu, Zhiyong
Abstract: This work investigated plutonium (Pu) isotopes in sediment cores collected from an alpine lake (Lake Heinongpo with 3779 m above sea level) in Southwestern China. 240 Pu/ 239 Pu atom ratios in all sediment samples showed the typical global fallout values of ∼0.18 without any influences from other Pu contaminant sources. 239+240 Pu activities with surface and subsurface maximums followed by exponential decline with sediment depth were respectively observed in the two sediment cores. The distinctive depth distributions of 239, 240 Pu in the lake sediments was attributed to the very slow sediment deposition rate due to the lack of terrestrial sediment input, while the alpine snowmelt input was the primary source of Pu in the lake sediments in addition to the direct atmospheric deposition. The total Pu inventory was estimated to be 56.3 ± 1.4 and 63.9 ± 0.8 Bq/m 2 respectively in the two sediment cores. The generally higher Pu inventory in the Lake Heinongpo compared with other reported lakes in similar latitude should be mainly attributed to their different Pu input passages. The advection-diffusion equation was further applied to evaluate the downward migration of Pu isotopes in the sediment cores and predict the future evolution of Pu distribution in the sediment cores. The fitted results indicated that the diffusion effect controlled the downward migration of Pu in the sediments, but this diffusive migration will not prevent the peak of global fallout Pu in undisturbed sediment cores from being a valuable time marker for sediment dating. Graphical abstract: Image 1 Highlights: Distribution of Pu in the lake Heinongpo was distinct from other lakes. Direct atmospheric deposition and snowmelt inflow were major Pu sources. Downward diffusive migration controlled the depth distribution of Pu in the lake. The diffusion of Pu in sediments will not affect the Pu peak as a dating marker.